DIGITAL MEDIA-BASED MINDFULNESS INTERVENTIONS IN EDUCATION SETTING: SYSTEMATIC LITERATURE REVIEW - Fuadina, Nabila; Febrianti, Thrisia (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Educational transformation in the use of technology is developing rapidly to optimize potential in the field of Education, one of the interventions that has been widely studied is mindfulness through digital platforms that have been effectively used in the clinical field. So this study aims to prove and analyze the effectiveness of digital media-based mindfulness interventions to support psychological development in the field of education. The method used in this study is a systematic literature review (SLR) with sources from Databases such as SpringerLink, PubMed, DOAJ, Wiley, and ScianceDirect, with publication years between 2020 and 2025. The selection of articles is based on the inclusion criteria of digital mindfulness interventions, participants come from the Education sector, namely students or college students as research subjects, and the use of experimental research designs. Screening was carried out using PRISMA, the results of the review produced 6 studies showing that digital mindfulness interventions for education in the form of Videoconferencing and podcasts, virtual reality (VR), app-based mindfulness, Mindfulness in a digital game, and StudiCare Mindfulness, can improve mindfulness, life satisfaction, self-regulation skills and mental health well-being for students and college students. Further research needs to explore with other variables and can be implemented in the population in Indonesia.